2022
DOI: 10.5644/ama2006-124.367
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Resistance Among Ischemic Stroke Patients and Its Risk Factors in Indonesia

Abstract: <p><strong>Objective</strong>. Clopidogrel is a common antiplatelet used as secondary prevention of ischemic stroke, known to have better efficacy than aspirin, with a equivalent safety profile. However, clopidogrel resistance is not uncommon but has not been widely studied in Asia. This study will further assess clopidogrel resistance and its risk factors.</p><p><strong>Materials and Methods</strong>. A cross-sectional study was conducted at Rumah Sakit Universitas, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…The number of participants resistant to clopidogrel in this study was 16 (14.3%). These results were consistent with those of previous ones in Indonesia, with no difference in frequency (9 people, 15.8%) [5]. This differs from the results of the two studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The number of participants resistant to clopidogrel in this study was 16 (14.3%). These results were consistent with those of previous ones in Indonesia, with no difference in frequency (9 people, 15.8%) [5]. This differs from the results of the two studies.…”
Section: Discussionsupporting
confidence: 90%
“…The study found that clopidogrel resistance and sex were significantly correlated, with women having a 2.8 times higher risk than men. These results were supported by a preliminary study that showed that men had an 80% lower risk of resistance than women [5]. In addition, studies by Price et al showed a significant correlation between sex and clopidogrel resistance [16].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Meanwhile, a previous study showed that clopidogrel resistance was high in stroke patients, varying from 28% to 44%. 22 In the pilot study by Hidayat et al, 23 the researchers found a consistently low resistance to clopidogrel. This showed that only 15% of clopidogrel metabolism still showed very good effectivity in Indonesia.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to determine an appropriate individual Aspirin dose to ensure optimal drug efficacy over time [ 19 ]. It has been reported that CR has not been extensively investigated in Asian communities to date [ 20 ]. This systematic review and meta-analysis was conducted on published papers on AR and CR in Iran as an example of a developing country in the Middle East region to portray understanding of the importance of this issue in clinical practice in developing countries.…”
Section: Introductionmentioning
confidence: 99%